2019
DOI: 10.1039/c9fo00307j
|View full text |Cite
|
Sign up to set email alerts
|

Peiminine inhibits the IL-1β induced inflammatory response in mouse articular chondrocytes and ameliorates murine osteoarthritis

Abstract: Osteoarthritis (OA) is a common arthrosis characterized by degeneration and inflammation of articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…In another report, sipeimine and peiminine from bulbs of F. wabuensis inhibited pro-inflammatory mediators in lipopolysaccharide (LPS) stimulated RAW 264.7 macrophage cells [ 15 ]. More recently, it was demonstrated that peimine relieved inflammatory effects in IL-1β-induced chondrocytes, indicating that peimine might be a potential therapeutic agent for osteoarthritis [ 16 ]. Antitussive, expectorant, and anti-inflammatory effects of several alkaloids, including sipeimine, chuanbeinone, peiminine, and peimine isolated from Bulbus Fritillaria cirrhosa were demonstrated in mice by using a phytochemical method [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another report, sipeimine and peiminine from bulbs of F. wabuensis inhibited pro-inflammatory mediators in lipopolysaccharide (LPS) stimulated RAW 264.7 macrophage cells [ 15 ]. More recently, it was demonstrated that peimine relieved inflammatory effects in IL-1β-induced chondrocytes, indicating that peimine might be a potential therapeutic agent for osteoarthritis [ 16 ]. Antitussive, expectorant, and anti-inflammatory effects of several alkaloids, including sipeimine, chuanbeinone, peiminine, and peimine isolated from Bulbus Fritillaria cirrhosa were demonstrated in mice by using a phytochemical method [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Damage of articular cartilage caused the changes in extracellular matrix of cartilage 3. Collagen II and aggrecan are the primary composition of the extracellular matrix in cartilage, and matrix metalloproteinase (MMPs) are very important for maintaining integrity of cartilage 4. Inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and IL-1β were considered to be important in inducing damage of articular cartilage 5,6.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and IL-1β were considered to be important in inducing damage of articular cartilage 5,6. IL-1β could regulate the differentiation and function of chondrocytes, which promotes the expression of MMPs; IL-1β then breaks down the cartilage matrix via inducing cell apoptosis 4,7. Therefore, inhibiting IL-1β-induced inflammation might be an effective therapeutic strategy for treating OA.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of the development of OA, abnormal metabolic dysfunction occurs in chondrocytes, and the synthesis of aggrecan and collagen II, the main components of chondrocyte extracellular matrix, are inhibited, while the synthesis of MMPs is increased, thus promoting the abnormal degradation of chondrocyte extracellular matrix (30)(31)(32). In addition, the large release of inflammatory factors such as IL-1β, IL-6, NO, PGE2 and TNF-α not only damages chondrocytes, but also induces extracellular matrix degradation, which is also an important reason for promoting the development of OA (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%